1990
DOI: 10.1159/000153923
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the Silent Gene for Plasma Cholinesterase

Abstract: Rocket immuno-electrophoresis and enzyme-linked immunosorbent assays were used to estimate the amount of cholinesterase present in 29 apparent silent homozygotes. 26 of these samples were segregated into four groups representing zero, very low, low and high levels of immunoreactive protein. These groups may represent the genotypes Es1, Es1, Es1, Et1, Εt1, Et1 and a new genotype E<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It is re markable that the E|k gene appears to be segregating in the 3 families each having the propositus with genotype E|SE|', and although this is a striking result we attach no significance to this segregation within these families until more data are avail able. Our earlier studies [Whittaker et al, 1990] indicated that 2 of the propositi (CH and MS) in families 5 and 7 appeared to be segregating the new silent gene E |\ The propositus 11-1 (KM) and her brother 11-2 in family 5 each show a high percentage protein binding ratio with MAb 2-1 and MAb 2-4, although the enzymic activities are very low, and from this we deduce that the E |' gene is segregating in this family. The ELISA results for their mother 1-1 with either MAb2-l or MAb 2-4 are low and so it is extremely improbable that she is segregating the E|x gene.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…It is re markable that the E|k gene appears to be segregating in the 3 families each having the propositus with genotype E|SE|', and although this is a striking result we attach no significance to this segregation within these families until more data are avail able. Our earlier studies [Whittaker et al, 1990] indicated that 2 of the propositi (CH and MS) in families 5 and 7 appeared to be segregating the new silent gene E |\ The propositus 11-1 (KM) and her brother 11-2 in family 5 each show a high percentage protein binding ratio with MAb 2-1 and MAb 2-4, although the enzymic activities are very low, and from this we deduce that the E |' gene is segregating in this family. The ELISA results for their mother 1-1 with either MAb2-l or MAb 2-4 are low and so it is extremely improbable that she is segregating the E|x gene.…”
Section: Resultsmentioning
confidence: 96%
“…Three families (2, 3 and 4) appear to be segregating both the E f and Ef genes in the propositus. One of them, 11-1 (KQ, family 2), has been phenotyped as E fE f in our earlier survey [Whittaker et al, 1990] and one of his siblings (11-4) has the same genotype. In this family the father 1-1 is segregating a usual gene E f but it is diffi cult to assign either the E f or Ef gene to the father 1-1 in preference to the mother 1-2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations